Modern Asian theatre and performance 1900-2000 - Wetmore, Kevin J. Jr. 1969-; Liu, Siyuan 1964 November 7-; Mee, Erin B. (Critical companions, 2014)
Modern Asian Theatre and Performance 1900-2000 is a ground-breaking survey, tracking the advent of modern drama in Japan, India, China, Korea and Southeast Asia. It considers the shaping power of realism and naturalism, the influence of Western culture, the relationship between theatrical modernisation and social modernisation, the links between so-called traditional and modern theatrical practices, the importance of hybridity in the development of modern drama, and how theatre operates in contemporary Asian society.--from back cover.